Employment Precariousness and Poor Mental Health : Evidence from Spain on a New Social Determinant of Health - Vives Vergara, Alejandra (2013)
Fil: Vives Vergara, Alejandra. Universitat Pompeu Fabra. Department of Political and Social Sciences; España. Comisión Nacional de Investigación Científica y Tecnológica. Fondo de Financiamiento de Centros de Investigación en ?reas Prioritarias. Pontificia Universidad Católica de Chile. Escuela de Medicina. Departamento de Salud Pública; Chile